Moral emotions and moral behavior - Tangney, June Price; Stuewig, Jeff; Mashek, Debra J (Annual review of psychology, 2007)
Moral emotions represent a key element of our human moral apparatus, influencing the link between moral standards and moral behavior. This chapter reviews current theory and research on moral emotions. We first focus on a triad of negatively valenced "self-conscious" emotions-shame, guilt, and embarrassment. As in previous decades, much research remains focused on shame and guilt. We review current thinking on the distinction between shame and guilt, and the relative advantages and disadvantages of these two moral emotions. Several new areas of research are highlighted: research on the domain-specific phenomenon of body shame, styles of coping with shame, psychobiological aspects of shame, the link between childhood abuse and later proneness to shame, and the phenomena of vicarious or "collective" experiences of shame and guilt. In recent years, the concept of moral emotions has been expanded to include several positive emotions-elevation, gratitude, and the sometimes morally relevant experience of pride. Finally, we discuss briefly a morally relevant emotional process-other-oriented empathy.